Gien, un château royal entre rupture et continuité avec l’œuvre de Louis XI - Mélinda Bizri; Sylvie Marchant; Christophe Perrault (Bulletin du Centre d’Études Médiévales d’Auxerre)
The castle of Gien built on the sidelines of the diocese of Auxerre has been the subject of a recent reassessment of the chronology of its construction and implantation. The authors of the article highlight the singular character of this building of the late fifteenth century whose constructive choices, studied from an archaeological and dendrochronological point of view are put in perspective in the productions of the same period. Thus, the use of materials – the brick in the first place –, their implementation with some experiments – upper chamber especially – and the construction site erasing the previous vestiges of the castral site, reflect the intentions of the sponsors. Anne de France, daughter of Louis XI, regent of the kingdom under the minority of Charles VIII, and Pierre de Bourbon pursue through this building installed at the junction of the duchies of Orleans, Burgundy and Bourbonnais the architectural and political work of Louis XI between rupture and continuity.